DAYA SAING EKSPOR PRODUK OLAHAN KAKAO INDONESIA DI NEGARA MALAYSIA PADA MASA PANDEMI COVID-19 - Seran, Ermina Anita; Taena, Werenfridus; Maulana, Achmad Subchiandi; Sipayung, Boanerges Putra (Agriprimatech, 2023)
Processed cocoa products were a source of foreign exchange for Indonesia both before the COVID-19 pandemic and during the pandemic. Malaysia is a neighboring country and Indonesia's strategic trading partner in cocoa and processed exports. This study analyzes export competitiveness and competitiveness factors of Indonesian processed cocoa products in Malaysia. This study uses annual time series data from 2005-2022. This research method uses descriptive quantitative analysis and gravity model analysis. The research results show that there has been a decline in the competitiveness of Indonesian processed cocoa products in Malaysia. The competitiveness of cocoa paste decreased by more than 50%. Domestic cocoa production, Malaysian GDP, and Indonesian GDP influence the value of Indonesian cocoa butter exports in Malaysia. Cocoa butter has shown an increase in export value during the Covid-19 pandemic. Malaysia's GDP and the COVID-19 pandemic have influenced the value of Indonesian cocoa paste exports to Malaysia. Cocoa paste has competitiveness both comparatively and competitively in the Malaysian market.